Pickering emulsion gel stabilized by milk fat globule membrane/pectin enhanced probiotic stability - Yu Ji; Yifan Wu; Yan Wang; Shuangshuang He; Yishan Jiang; Xin Li; Liupeng Wang; Qian Xu; Lili Zhang; Hao Wang (Food Chemistry: X)
The milk fat globule membrane (MFGM) has been shown to improve probiotic survival in the gastrointestinal tract. However, emulsions stabilized through electrostatic interactions between MFGM and polysaccharides for probiotic encapsulation remain unexplored. This study established optimal conditions for creating MFGM-Pectin (CP) emulsions. At pH 4.0, a MFGM/CP ratio of 1 produced the smallest particle size and the highest zeta potential, ideal for emulsion stabilization. We evaluated the effects of varying complex concentrations and oil phase ratios on emulsion properties. The results indicate that CP significantly affects the apparent viscosity, oxidative stability, centrifugal stability, storage stability, and antioxidant activity of MFGM-CP emulsions. Furthermore, the encapsulation of LGG within the emulsion improved its survival and storage stability in simulated gastrointestinal fluids. These findings suggest that MFGM is a promising material for probiotic encapsulation and provide a foundation for developing MFGM-based products containing probiotics or other active ingredients.